HUBUNGAN TINGKAT PENDIDIKAN DAN PEKERJAAN DENGAN PENGETAHUAN TENTANG PENCEGAHAN COVID-19 DI KECAMATAN BANJARMASIN UTARA TAHUN 2021 - Muhammad Ihrammuf Tezar; Farida Heriyani; Lisda Hayatie; Meitria Syahadatina Noor; Edyson Edyson (Homeostasis, 2022)
One of the big reason of the rise in COVID-19 instances is public noncompliance with health protocol implementation. What needs to be enhanced is public awareness about COVID-19 transmission prevention. The research purposes is to analyze the association between education level and occupation in accordance to COVID-19 prevention in North Banjarmasin sub-district. The research method is analytic observational with a cross-sectional approach. Sampling used a purposive sampling method with the size of 50 people from North Banjarmasin sub-district who met two criterias, namely inclusion and exclusion. According to the data gathered in this study, 45 people (90%) had a high education, while 5 people (10%) had a low education. On the occupation, there were 20 people (40%) working and 30 people (60%) not working. The results showed 39 people (78%) had good knowledge and 11 people (22%) had bad knowledge. Fisher's test results shows that the correlations between education level and knowledge have a p value of 0.006 (p value < 0.05) with PR = 5.142857. And another results of the Fisher’s test for the correlations between occupation and knowledge have a p value of 0.489 (p value > 0.05). The results shown a significant correlations between education level and knowledge of COVID-19 prevention, and there is no remarkable correlations in occupation with knowledge about COVID-19 prevention